The reliability of spread foundations designed to Eurocode 7 - Forrest, William Stephen (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2011)
The main objective of the research work described in this thesis is to evaluate the reliability of spread foundations designed to Eurocode 7 using the partial factors and Design Approaches adopted in the Irish National Annex for the implementation of Eurocode 7 in Ireland. As part of this research, the First Order Reliability Method is used to determine the reliability of designs using the Irish National Annex. The Irish National Annex is also compared to the National Annexes of some other European countries. It is shown that the three Design Approaches adopted in the Irish National Annex offer a more consistent level of reliability than the traditional Factor of Safety methods. The target reliability indices are achieved in many cases, but the reliability is a function of the characteristic value chosen in the design and it is not always sufficient to take the characteristic value as the 95% confidence in the mean, as target reliabilities may not be achieved using this value. The appropriate characteristic value to be used in design depends on whether the foundation fails involving a local or global failure domain. A foundation can be considered to fail with a local failure mechanism when the foundation widths are small. For larger foundation widths, a greater amount of soil needs to be mobilised and therefore the failure mechanism can be considered to be a global failure.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin